Influence of age and fitness level on β-endorphin response to acute aerobic exercise in healthy men - Marano, Luigi; Tommasini, Ester; Missaglia, Sara; Vago, Paola; Rampinini, Ermanno; Bosio, Andrea; Morelli, Andrea; Pecci, Claudio; Mordente, Alvaro; Tavian, Daniela (Sport sciences for health, 2025)
Purpose This study aimed to investigate the time course of β - endorphin (β-EDP) levels in healthy males following an acute exercise, while considering their age and physical fitness (PF) level. Methods Participants ( N = 29, 20–65 years) were categorized in good PF young adult (YA1), excellent PF young adult (YA2), and excellent PF middle-aged adult (MA) group, depending on peak oxygen uptake and age. They underwent a maximal incremental cycling test, with blood samples collected at baseline (T0), 15 min (T1), and 24 h post-exercise (T2). Serum β-EDP levels were measured using an ELISA kit. Results Significant increases in β-EDP levels were observed from T0 to T1 in all enrolled subjects. In YA1, levels rose from 170.1 to 202.5 pg/ml ( p < 0.001), in YA2 from 188.4 to 230.3 pg/ml ( p < 0.05), and in MA level increased from 153 to 189.3 pg/ml ( p < 0.01). YA2 showed higher levels of β-EDP than MA in any time point ( p < 0.05). All groups displayed a significant decrease of β-EDP from T1 to T2. Comparison between groups revealed that age significantly influenced baseline β-EDP levels, with notable differences between young and middle-aged individuals. Noteworthy, MA with excellent PF presented similar β-EDP levels to young with good PF. Conclusion Acute exercise triggers a notable but transient elevation of serum β-EDP levels in both young and middle-aged adults, with the latter exhibiting lower baseline levels. Additionally, our findings suggest that age may have a greater influence on β-EDP secretion, both at rest and after physical exercise compared to PF level.